1999
DOI: 10.1021/ie980576l
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and Noncatalytic Wet Oxidation

Abstract: The wet oxidation of organic compounds composed only of C, H, and O, dyes, amides, and water-soluble polymers is discussed to clarify the basic nature of this process. The reactivity of the organic compounds composed of C, H, and O, dyes, and some amides was correlated well with their carbon content in the molecule (C/MW) or carbon content in their skeletal structure (C/MW‘). This C/MW index can be applied to roughly estimate the behavior of wastewaters containing various organic compounds. Polymers are easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
186
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(191 citation statements)
references
References 31 publications
2
186
0
1
Order By: Relevance
“…WAO performance can be improved by the addition of homogeneous [5,6] or heterogeneous [4] catalysts at subcritical conditions or at severe 'supercritical' operating conditions [7,8]. Alternatively, low temperature oxidation processes replace oxygen by stronger oxidants such as O 3 [9,10] or H 2 O 2 [9,11,12] in combination with an energy input to form reactive OH-radicals [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…WAO performance can be improved by the addition of homogeneous [5,6] or heterogeneous [4] catalysts at subcritical conditions or at severe 'supercritical' operating conditions [7,8]. Alternatively, low temperature oxidation processes replace oxygen by stronger oxidants such as O 3 [9,10] or H 2 O 2 [9,11,12] in combination with an energy input to form reactive OH-radicals [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, low temperature oxidation processes replace oxygen by stronger oxidants such as O 3 [9,10] or H 2 O 2 [9,11,12] in combination with an energy input to form reactive OH-radicals [13,14]. Several reviews on catalytic and non-catalytic WAO [4,5,[15][16][17][18][19], supercritical water oxidation (SCWO) [7,8,[20][21][22] and advanced oxidation processes (AOP) [23][24][25] are now available in literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to overcome the problem of recovery/removal of the toxic catalysts from the final effluent, heterogeneous catalysts such as transition metal oxides, c-alumina supported with CuO, copper, manganese, and lanthanum oxides on a 0045-6535/$ -see front matter Ó 2004 Elsevier Ltd. All rights reserved. doi: 10.1016/j.chemosphere.2004.11.004 zinc aluminate spinel, and multicomponent oxides CuO AE ZnO, Ru/Ce, Mn/Ce and Co/Bi have been developed (Imamura, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The wet air oxidation of acetic acid was studied by Merchant [46] and it was found that only 7% COD reduction was achieved at 275°C in 5 hours. The WAO of both formic acid and acetic acid were studied by Imamura [24] at 220°C and partial oxygen pressure of 3 MPa in 2 hours. 99% TOC reduction and 100%…”
mentioning
confidence: 99%